Kesalahan Berbahasa pada Teks Deskripsi Siswa Sekolah Menengah Atas - Siagian, Irwan; Sumirah, Sumirah; Nisa, Khoirun (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
In everyday life, language activities are common. This activity is important in establishing communication between people, both verbally and in writing. When involved in language activities, language errors often appear, resulting in an analysis of these errors. This research aims to describe the types of language errors that appear in descriptive texts made by high school students. The method used in research is qualitative description. The objects used in this research are documents written by high school students. Based on the research, it can be concluded that there are (1) spelling errors which include punctuation errors, letter usage errors and word writing errors, (2) phonological errors which include phoneme deletion errors, (3) morphological errors which include errors in writing prepositions and less effective word selection, (4) syntactic errors which include wasting words, use of conjunctions, choice of phrases and sentence structure, (5) semantic errors which include word ambiguity and formal word choice.